Land use intensity and land occupation of utility-scale photovoltaic power plants in continental Portugal - Távora, J.; Cortinhal, M. J.; Meireles, M. (37th European Photovoltaic Solar Energy Conference and Exhibition, 2020)
Details about Portuguese PV stations are scarce: no public access is provided to project files and environmental impact assessments (EIA) - public-domain information - are mandatory only for power plants of 50 MW or higher capacity, a small minority. In our research, we measured the land use intensity (LUI) of utility-scale PV power plants in continental Portugal and estimated their future land occupation from the capacity additions forecast by the government and from the expected future improvements in LUI due to the increase in PV panel efficiency. A novel method, with land occupation depending simultaneously on the evolution of capacity and panel efficiency, was developed for the purpose. We found 3.336 ha/MW for the average LUI of all stations in operation in continental Portugal, with the LUI varying with mounting type. For land occupation by PV plants in 2050 we found large areas albeit small when compared with other land cover types, e.g. 30 000 hectares would be 1.3% and 0.9% of the current areas dedicated to agriculture and forestry, respectively. However, with EIAs required only for large stations there will be opportunities for land-use conflicts and deep landscape alterations.